A CLINICAL ANALYSIS OF DISORDERED GROWTH AND DEVELOPMENT IN CHILDREN WITH CONSTIPATION (International journal of medical sciences, 2026)
Constipation is a disorder of bowel function characterized by increased intervals between bowel movements compared to the individual norm or by a systematically insufficient bowel movement. In children, unlike adults, increased intervals between bowel movements are of particular importance. Moreover, many publications note that stool frequency depends on the child's age and, accordingly, the number of feedings, and can be quite variable.